Coxiella burnetii seroprevalence and associated risk factors in dairy and mixed cattle farms from Ecuador - Saa, L. (2017)
Q fever is a zoonotic disease caused by Coxiella burnetii, a bacterial agent for which ruminants are the main reservoir. An extensive cross-sectional study to determine the seroprevalence of and associated risk factors for Q fever was performed in dairy and mixed (dairy-beef) cattle herds in Ecuador. A total of 2668 serum samples from 386 herds were analyzed using an ELISA. In addition, a questionnaire with 57 variables related to management, feeding, facilities, biosecurity and animal health was completed for every cattle farm. A Generalized Estimating Equations model was used to determine the factors associated with C. burnetii seropositivity.The true prevalence of C. burnetii seropositivity in dairy and mixed cattle from Ecuador reached 12.6% (CI95%: 11.3-13.9%). The herd prevalence was 46.9% (181/386) (CI95%: 41.9-51.9%), and the within herd prevalence ranged between 8% and 100% (mean: 25.0%; Q1: 12.5%, Q2: 25.0%, Q3: 37.5%). Four factors were included in the GEE model for C. burnetii seropositivity: age of the cattle (OR: 1.01; CI95%: 1.006-1.014), feeding of calves with milk replacers (OR: 1.94; CI95%: 1.1-3.3), bovine respiratory syncytial virus seropositivity (OR: 1.54; CI95%: 1.1-2.3), and disinfection of the umbilical cord (OR: 0.60; CI95%: 0.4-0.9).